(untitled) - Beach, Earl Francis (New York, 1957)
This book is a contribution to the solution of both of these problems. There is no attempt to add to current knowledge of mathematical economics or statistics, but great care has been taken to put this knowledge in a form that can be readily digested by beginners.
Keywords: Economics,Kinh tế; Mathematical models,Mô hình toán học